the Prevailing 2013 Curriculum in Junior High School Practice: Teacher Perspective - Bunyamin Bunyamin; Khoerul Umam (JETL (Journal of Education, Teaching and Learning), 2019)
The 2013 Curriculum has been implemented in various schools in Jakarta. Although, the concept has been debated among teachers, and practitioners, some private and public schools in Jakarta have fully implemented this curriculum. The main purpose of this study was to examine teachers understanding of the prevailing 2013 Curriculum. This study used mix methods. The quantitative method was used to examine the teachers’ competence about the 2013 Curriculum, while the qualitative method was used to strengthen and explore teachers’ responses about curriculum in classroom practices. There were three different aspects that evaluated such as training period, classroom practice, and students' classroom engagement. The participant included 125 junior high school teachers from different parts of Jakarta. Data were collected through an online survey with a Likert scale. Data were analyzed by descriptive statistics. The result of this study reported that teachers have enough time to get their training but they need extra time to prepare for classroom practice. Students who be engaged the 2013 Curriculum in classroom practice have been supported to work collaboratively with their peers.  Teachers need to be prepared such as equipment, classroom plan, book for the teacher, and time for meeting among their peer teaching. In the class practice, teachers need allotted time to prepare for teaching and examination.